2016
DOI: 10.1002/nau.23155
|View full text |Cite
|
Sign up to set email alerts
|

The effect of doxazosin and sildenafil citrate combination on bladder tissue contractility, alpha adrenergic receptor, and iNOS subtype expression in a male rat model of partially bladder outlet obstruction

Abstract: Contractile changes of rat bladder tissue due to PUO were prevented by sildenafil or doxazosin alone or in combination where combination treatment did not provide any additional advantage. Further studies are needed to clarify the role of phosphodiesterase inhibitors and combination treatment in the treatment of LUTS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…As shown in previous studies, the role of cytokines including alpha-blockers, antimuscarinics, and β-Adrenergic receptors during BOO has been well-established (Dale et al, 2014;Gumrah et al, 2017;Yamada et al, 2018). In addition, TGF-β signaling could stimulate fibrotic changes in BSMCs after BOO, and miR-133 could modulate TGF-β-induced BSMC phenotypic changes by targeting CTGF (Duan et al, 2015).…”
Section: Introductionmentioning
confidence: 75%
“…As shown in previous studies, the role of cytokines including alpha-blockers, antimuscarinics, and β-Adrenergic receptors during BOO has been well-established (Dale et al, 2014;Gumrah et al, 2017;Yamada et al, 2018). In addition, TGF-β signaling could stimulate fibrotic changes in BSMCs after BOO, and miR-133 could modulate TGF-β-induced BSMC phenotypic changes by targeting CTGF (Duan et al, 2015).…”
Section: Introductionmentioning
confidence: 75%
“…Sildenafil is a phosphodiesterase 5 (PDE-5) inhibitor; it inhibits the breakdown of cGMP thus prolongs the action of NO in smooth muscles [30]. Gumrah et al (2017) proved that sildenafil reduced bladder contractility in rats and Aizawa et al (2017) showed that sildenafil may improve bladder storage in female rats by exhibiting an inhibitory role on the bladder afferent transduction [31,32].…”
Section: Introductionmentioning
confidence: 99%